The addition of duck egg yolk in skim milk – fructose extender maintains sperm motility and viability of Muscovy duck (Cairina moschata) at 5°C storage - Isti Annisa Ramahtia; Tatik Hernawati; Tri Wahyu Suprayogi; Tjuk Imam Restiadi; Djoko Legowo; Samuel Inioluwa Akeju (Universitas Airlangga, 2024)
This study aimed to determine the addition of duck egg yolk in skim milk – fructose extender on sperm motility and viability of Muscovy duck (Cairina moschata) at 5°C storage. Ejaculates of Muscovy duck were divided into four portions equally. The first portion was for the control group (diluted in skim milk – fructose extender), and the second, third, and fourth portions were for the treatment groups of T1, T2, and T3 (diluted in skim milk – fructose extender added with 2.5, 5.0, and 7.5% v/v duck egg yolk). Sperm motility and viability were evaluated two hourly until the motility percentage reached 40%. The data were analyzed using ANOVA and Duncan test. The result showed that the highest percentage of spermatozoa motility and viability (p<0.05) was in the T2 group compared to the other groups. It could be concluded that the Muscovy duck semen extended in skim milk - fructose with 2.5 to 7.5% egg yolk of duck qualified for artificial insemination at storage up to 10 hours in 5°C storage.